Assessing the accommodation response after near visual tasks using different handheld electronic devices - Moulakaki, Aikaterini I.; Recchioni, Alberto; Águila-Carrasco, Antonio J. Del; Esteve-Taboada, José J.; Montés-Micó, Robert (Arquivos brasileiros de oftalmologia, 2017)
To assess the accommodation response after short reading periods using a tablet and a smartphone as well as determine potential differences in the accommodation response at various stimulus vergences using a Hartmann- Shack aberrometer. Eighteen healthy subjects with astigmatism of less than 1 D, corrected visual acuity of 20/20 or better, and normal findings in an ophthalmic examination were enrolled. Accommodation responses were obtained under three different conditions: accommodation system of the eye relaxed and visually stressed with a tablet and an smartphone for 10 min, at a distance of 0.25 m from the subject's eyes. Three measurements of accommodation response were monocularly acquired at stimulus vergences ranging from 0 to 4 D (1-D step). No statistically significant differences were found in the accommodation responses among the conditions. A moderate but gradually increasing root mean square, coma-like aberration was found for every condition. Conversely, the spherical aberration decreased as stimulus vergences increased. These outcomes were identified in comparison to the one-to-one ideal accommodation response, implying that a certain lag value was present in all stimulus vergences different from 0 D. The results support the hypothesis that the difference between the ideal and real accommodation responses is mainly attributed to parameters associated with the accommodation process, such as the near visual acuity, depth of focus, pupil diameter, and wavefront aberrations. The wavefront aberrations were dependent on the 3-mm pupil size selected in this study. The accommoda tion response was not dependent on the electronic device employed in each condition, and it was mainly associated with young age and level of amplitude of accommodation of the subjects.